Antibacterial activity of green silver nanoparticles on the in vitro pathogen infected Eucalyptus pellita plant - Sawalha, Hanadi; Ahmad, Siti Aqlima; Shaharuddin, Noor Azmi; Sanusi, Ruzana; Azzeme, Azzreena Mohamad; Naganthran, Ashwini; De Silva, Catrenar; Abiri, Rambod (Springer Science and Business Media B.V., 2024)
The antimicrobial activity of green silver nanoparticles (AgNPs) offers a promising approach for combating in vitro pathogen infections in Eucalyptus pellita (E. pellita) plants. This strategy provides an environmentally sustainable method to improve plant health and resistance. The effect of green synthesised AgNPs on the pathogen-infected in vitro regenerated E. pellita plantlets was examined. Firstly, shoots regenerated from cotyledonary leaf explants of E. pellita were examined in vitro through a direct organogenesis technique using murashige and Skoog (MS) medium supplemented with different concentrations (0.4, 1.3, 2.2, 3.1 and 3.9 µM) of 6-benzylaminopurine (BAP). The elongated shoots were rooted in vitro using ½ MS medium supplemented with different concentrations (0.5, 1, 1.5, 2 and 2.5 µM) of indole-3-butyric acid (IBA). The highest shoot formation from cotyledonary leaves was observed in the MS media supplemented with 2.2 µM BAP, followed by 3.1 µM BAP giving a mean of 7.4 and 6 shoots per explant, respectively. The highest root formation was observed in the ½ MS media supplemented with 1.5 µM IBA, yielding an average of 17.47 roots per explant. Secondly, the antibacterial effect of green AgNPs on tissue-cultured plants was examined by inoculating green AgNPs and three bacterial strains (Bacillus sp. strain EUUPM1, Pantoea dispersa strain EUUPM3 and Pantoea dispersa strain EUUPM2). The results showed that green AgNPs controlled bacterial growth at 100 ppm concentration. The focal point of the current research is to use of green synthesised AgNPs as an efficient antibacterial agent that particularly targets in vitro pathogen infections in E. pellita plants. Thus, this study finds that green AgNPs possess potent antibacterial activity and could therefore be developed as a promising antimicrobial agent for the treatment of bacterial infections, including gram-positive and gram-negative bacteria.